Metal-Semiconductor-Metal Photodetectors on a GeSn-on-Insulator Platform for 2 µm Applications - Bongkwon Son; Yiding Lin; Kwang Hong Lee; Joe Margetis; David Kohen; John Tolle; Chuan Seng Tan (IEEE Photonics Journal, 2022)
In this work, the metal-semiconductor-metal photodetectors were demonstrated on the Ge0.91Sn0.09-on-insulator (GeSnOI) platform. The responsivity was 0.24 and 0.06 A/W at wavelengths of 1,600 and 2,003 nm, respectively. Through a systematic study, it is revealed that the photodetectors can potentially detect wavelength beyond 2,200 nm. The dark current density was measured to be 4.6 A/cm2 for GeSnOI waveguide-shaped photodetectors. The 3 dB bandwidth was observed to be 1.26 and 0.81 GHz at 1,550 and 2,000 nm wavelengths, respectively. This work opens up an opportunity for low-cost 2 µm wavelength photodetection on the GeSn/Ge interface-free GeSnOI platform.